PENGARUH PROMOSI DAN HARGA TERHADAP VOLUME PENJUALAN YAMAHA SCORPIO Z Di PT. ALFA SCORPII SENTRAL YAMAHA-MEDAN - Dhita Adriani Rangkuti (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This paper is to investigate whether promotion and price of motor cycle namely Yamaha Scorpion Z effect to elevate its volume sales at PT. Alfa Scorpii Sentral Yamaha Medan. The document of the company throughout year 2016 is used as an instrument in data collection and it is main data, while the data gained from interview section is used for supporting main data which is quantitative and statistical data. Hence, the method of multiple linier regressions is used to analyze the data. The results show that partially the promotion variable effects significantly to elevate sale volume of the Yamaha Scorpio Z (series cw) at PT. Alfa Scorpii Sentral Yamaha Medan. Nevertheless, the price does not give impact significantly to increasing sale volume of the Yamaha Scorpio Z (seri cw) at PT. Alfa Scorpii Sentral Yamaha Medan and simultaneously, promotion and price do not give impact to elevate to sale volume of Yamaha Scorpio Z (serrial cw) at PT. Alfa Scorpii Sentral Yamaha Medan